Hypovitaminosis D and Mild Hypocalcaemia Are Highly Prevalent among Young Vietnamese Children and Women and Related to Low Dietary Intake - Laillou, Arnaud (Public Library of Science, 2013)
INTRODUCTION: In many developing countries including Vietnam, data are lacking on vitamin D and calcium deficiencies whereas those deficiencies can play an important role in the development of bone health and possibly non-communicable diseases. The purpose of this study was to determine the overall prevalence of vitamin D and calcium deficiencies in women and young children and their nutritional related risk factors. METHODS: A cross-sectional study conducted among 595 women of reproductive age and 532 children <5 years from 19 provinces of Vietnam. For each individual, data concerning daily diet, socioeconomic group, anthropometric status were obtained, and plasma concentrations of calcium and vitamin D were measured. RESULTS: The prevalence of hypovitaminosis D status was very high, with the prevalence of vitamin D deficiency (25(OH)D<30 nmol/L) and insufficiency (25(OH)D between 30–49.9 nmol/L) being 17% and 40% in women and 21% and 37% in children, respectively. Using more liberal cut-off of 75 nmol/L, approximately 90% of the women and children were classified as having hypovitaminosis D. Overweight/obese women had a 2 times lower risk (OR = 0.46, [0.24–0.90]) for vitamin D deficiency than non-overweight and non-obese women. No participant had severe calcium deficiency but moderate and mild hypocalcaemia (plasma calcium concentrations between 1.15-0.9 mmol/L for mild deficiency and between 0.9-0.8 mmol/L for moderate deficiency) affected respectively 14% and 83% of the women with 97% of the children having mild hypocalcaemia. Women and children consumed about 1% of the Institute of Medicine (IOM) recommended nutrient intake (RNI) for vitamin D and less than 43% of the RNI for calcium. CONCLUSION: Our study suggests that calcium and vitamin D deficiencies represent a major public health concern in Vietnam. Thus, actions to improve the vitamin D and calcium status of the Vietnamese population should be considered.